Preventing chronic disease in overweight and obese patients with low health literacy using eHealth and teamwork in primary healthcare (HeLP-GP): a cluster randomised controlled trial. Issue 11 (30th November 2022) - Parker, Sharon M; Barr, Margo; Stocks, Nigel; Denney-Wilson, Elizabeth; Zwar, Nicholas; Karnon, Jon; Kabir, Alamgir; Nutbeam, Don; Roseleur, Jackie; Liaw, Siaw-Teng; McNamara, Carmel; Frank, Oliver; et al.
Abstract : Objectives: To evaluate a multifaceted intervention on diet, physical activity and health literacy of overweight and obese patients attending primary care. Design: A pragmatic two-arm cluster randomised controlled trial. Setting: Urban general practices in lower socioeconomic areas in Sydney and Adelaide. Participants: We aimed to recruit 800 patients in each arm. Baseline assessment was completed by 215 patients (120 intervention and 95 control). Intervention: A practice nurse-led preventive health check, a mobile application and telephone coaching. Primary and secondary outcome measures: Primary outcomes were measured at baseline, 6 and 12 months, and included patient health and eHealth literacy, weight, waist circumference and blood pressure. Secondary outcomes included changes in diet and physical activity, preventive advice and referral, blood lipids, quality of life and costs. Univariate and multivariate analyses of difference-in-differences (DiD) estimates for each outcome were conducted. Results: At 6 months, the intervention group, compared with the control group, demonstrated a greater increase in Health Literacy Questionnaire domain 8 score (ability to find good health information; mean DiD 0.22; 95% CI 0.01 to 0.44). There were similar differences for domain 9 score (understanding health information well enough to know what to do) among patients below the median at baseline. Differences were reduced and non-statistically significant at 12 months. There was a small improvement in diet scores at 6 months (DiD 0.78 (0.10 to 1.47); p=0.026) but not at 12 months. There were no differences in eHealth literacy, physical activity scores, body mass index, weight, waist circumference or blood pressure. Conclusions: Targeted recruitment and engagement were challenging in this population. While the intervention was associated with some improvements in health literacy and diet, substantial differences in other outcomes were not observed. More intensive interventions and using codesign strategies to engage the practices earlier may produce a different result. Codesign may also be valuable when targeting lower socioeconomic populations. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN 12617001508369) (http://www.ANZCTR.org.au/ACTRN12617001508369.aspx ). Trial protocol: The protocol for this trial has been published (open access; https://bmjopen.bmj.com/content/8/6/e023239 ).